The Right Supramarginal Gyrus Is Important for Proprioception in Healthy and Stroke-Affected Participants: A Functional MRI Study - Ben-Shabat, Ettie; Matyas, Thomas A.; Pell, Gaby S.; Brodtmann, Amy; Carey, Leeanne M. (Frontiers in Neurology, 2015)
Human proprioception is essential for motor control, yet its central processing is still debated. Previous studies of passive movements and illusory vibration have reported inconsistent activation patterns related to proprioception, particularly in high order sensorimotor cortices. We investigated brain activation specific to proprioception, its laterality and changes following stroke. Twelve healthy and three stroke affected individuals with proprioceptive deficits participated. Proprioception was assessed clinically with the Wrist Position Sense Test, and participants underwent functional MRI (fMRI) scanning. An event-related study design was used, where each proprioceptive stimulus of passive wrist movement was followed by a motor response of mirror copying with the other wrist. Left (LWP) and right (RWP) wrist proprioception were tested separately. Laterality indices (LI) were calculated for the main cortical regions activated during proprioception. We found proprioception-related brain activation in high order sensorimotor cortices in healthy participants especially in the supramarginal gyrus (SMG LWP z=4.51, RWP z=4.24) and the dorsal premotor cortex (PMd LWP z=4.10, RWP z=3.93). Right hemispheric dominance was observed in the SMG (LI LWP mean 0.41, SD 0.22; RWP 0.29, SD 0.20), and to a lesser degree in the PMd (LI LWP 0.34, SD 0.17; RWP 0.13, SD 0.25). In stroke affected participants the main difference in proprioception-related brain activation was reduced laterality in the right SMG. Our findings indicate that the SMG and PMd play a key role in proprioception probably due to their role in spatial processing and motor control respectively. The findings from stroke affected individuals suggest that decreased right SMG function may be associated with decreased proprioception. We recommend that clinicians pay particular attention to the assessment and rehabilitation of proprioception following right hemispheric lesions